Asperger syndrome in adolescence : living with the ups, the downs, and things in between - Willey, Liane Holliday (J. Kingsley Publishers, 2003)
Childhood and adult experiences of individuals with Asperger Syndrome (AS) are becoming increasingly well documented, yet the crucial formative teenage years have, so far, been neglected. Adolescence is a difficult time for any teenager, but when you have Asperger Syndrome this already emotionally complex time of life becomes all the more challenging. Reflecting the views of parents, professionals and those with AS themselves, this book tackles issues that are pertinent to all teenagers, such as sexuality, depression and friendship, as well as discussing topics like disclosure and therapeutic.